Patterns and determinants of postpartum physical activity among women attending postnatal care in Lusaka, Zambia: A cross-sectional study. - Chela Singoyi, Jane; Moyo, Geoffrey; Nkhata, Loveness Anila (Student’s Journal of Health Research Africa, 2026)
Background: Postpartum physical activity is vital for maternal recovery and long-term health, but participation rates are low, particularly in low- and middle-income countries like Zambia. This study focused on assessing the knowledge, attitudes, practices, and factors influencing postpartum physical activity among women receiving postnatal care in Lusaka, highlighting the need for more quantitative evidence in this area. Methods: A facility-based cross-sectional study involving 420 postpartum women at four public health facilities in Lusaka District, assessed their sociodemographic characteristics, obstetric history, knowledge, attitudes, physical activity practices, barriers, and healthcare provider counselling. Data was collected through a structured questionnaire, and multivariable logistic regression was utilized to identify factors associated with adherence to World Health Organization physical activity recommendations. Results: The mean age of participants was 28.4±5.6 years. Only 24.3% (n=102) of women met recommended levels of postpartum physical activity. Although 38.6% (n=162) demonstrated good knowledge and 45.7% (n=192) reported positive attitudes towards physical activity, a substantial knowledge-practice gap existed. Multivariable analysis revealed that vaginal delivery (AOR=2.34, 95%CI: 1.45-3.78, p<0.001), tertiary education (AOR=2.87, 95%CI: 1.52-5.41, p=0.001), good knowledge (AOR=2.15, 95%CI: 1.18-3.92, p=0.012), positive attitudes (AOR=1.98, 95%CI: 1.05-3.74, p=0.035), primiparity (AOR=1.76, 95%CI: 1.09-2.84, p=0.020), and receipt of healthcare provider counselling (AOR=3.21, 95%CI: 2.01-5.13, p<0.001) were independently associated with higher physical activity participation. Major barriers included lack of time (68.3%), fatigue (62.1%), cultural beliefs about postpartum rest (54.8%), and absence of healthcare provider guidance (55.7%). Conclusion: Postpartum physical activity among women in Lusaka is low, indicating a knowledge-practice gap. The strongest modifiable predictor is healthcare provider counselling. Enhancing counselling in routine postnatal care, particularly for women recovering from caesarean sections, could effectively improve maternal physical activity engagement. Future nationwide longitudinal studies should assess pregnancy-to-postpartum physical activity trends.